PERAN PEMBENAH TANAH YANG BERBASIS AMPAS TEH TERHADAP PERTUMBUHAN TANAMAN WIJEN ( Sesamum indicum, L.) - Sarwono, Dewi Ratna Nurhayati & (Joglo, 2017)
One of the obstacles in cultivation are appropriate planting medium condition, which is supported by the availability of water and nutrients for plants. In order to increase crop productivity needs the technology applied to the condition of the growing media physically, Thursday and biological met for plant growth and development through the use of ground-based pembenah teacup potential for improvement of the growing media / Biological Soil Amendments. So as to optimize the planting medium to improving the properties of soil physical, chemical, biological, can hold water and provide nutrients, which then make it as a source of plant needs in a sustainable manner on a sesame plant. This study will be conducted at the experiment station. FP Unisri in March to September 2016. The design used was completely randomized design (CRD) factorial with four replications. Factors such treatment of a wide variety and combination pembenah ground sesame dregs of tea. The varieties used are Winas Winas 1 and 2. Combination pembenah latosol soil to soil type, in the form of tea waste consists of five types (control, 200 g teacup, tea dregs 300 g, 200g + manure 100 g, 300 g teacup + 100 g manure). The observations made are: observation of soil fertility, physiological and agronomic parameters. The results show that research, plant growth winas Winas 1 and 2 provide real results against a control. The dose of 200 g teacup + 100 g manure gives the best result for plant growth and Winas sesame Winas 1 2Keywords: tea dregs, Biological Soil Amendments, observations of soil fertility, physiological and agronomic parameters.